Strengthening Religious Moderation Through the Core Values of Islamic Boarding School Education - Huda, Miftahul (Letiges, 2024)
This research explores how the core values embedded in Islamic boarding school education contribute to developing a moderate and inclusive form of Islam. This study will focus on the impact of these values on individuals within the pesantren environment and, consequently, on broader societal dynamics. The approach employed in this research is qualitative, precisely a literature review type, which is a problem-solving method that seeks data sources, both primary and secondary, in the form of books, journals, essays, articles, and other document data. Data analysis in this study used content analysis techniques. The study results found that Islamic boarding school education is a vital moral force in Indonesia's education system, shaping unique social values like local wisdom within its distinct subculture. The research highlights strengthening these values as a novel foundation for Islamic moderation, presenting two education models. The innovative use of social construction theory identifies stages in value transmission, habitualization, and transformative shifts, enriching discourse on Islamic education. Urging a redefinition of education, the study emphasizes the coexistence of Islamic values with global trends. Pursuing moderate Islamic education aligns with togetherness, justice, tolerance, consultation, and social liberation, marking a significant stride in educational research and practice. This research explores the process of transmitting social values in Islamic boarding schools with a conceptual foundation of moderate Islamic education, emphasizing an inclusive paradigm for Islamic values alongside global trends.